New Horizons in Diabetic Neuropathies: An Updated Review on their Pathology, Diagnosis, Mechanism, Screening Techniques, Pharmacological, and Future Approaches - Aziz, Namra; Dash, Biswajit; Wal, Pranay; Kumari, Prachi; Joshi, Poonam; wal, Ankita (Current Diabetes Reviews, 2024)
Background: One of the largest problems for global public health is diabetes mellitus (DM) and its micro and macrovascular consequences. Although prevention, diagnosis, and treatment have generally improved, its incidence is predicted to keep rising over the coming years. Due to the intricacy of the molecular mechanisms, which include inflammation, oxidative stress, and angiogenesis, among others, discovering treatments to stop or slow the course of diabetic complications is still a current unmet need. Methods: The pathogenesis and development of diabetic neuropathies may be explained by a wide variety of molecular pathways, hexosamine pathways, such as MAPK pathway, PARP pathway, oxidative stress pathway polyol (sorbitol) pathway, cyclooxygenase pathway, and lipoxygenase pathway. Although diabetic neuropathies can be treated symptomatically, there are limited options for treating the underlying cause. Result: Various pathways and screening models involved in diabetic neuropathies are discussed, along with their possible outcomes. Moreover, both medicinal and non-medical approaches to therapy are also explored. Conclusion: This study highlights the probable involvement of several processes and pathways in the establishment of diabetic neuropathies and presents in-depth knowledge of new therapeutic approaches intended to stop, delay, or reverse different types of diabetic complications.
Keywords: neuropathic pain